Impact of financial education towards financial well-being: a case study on credit counselling and debt management agency (AKPK) financial education - Nirmala, Supramaniam (2019)
Financial education is seen as a solution in improving financial literacy which will then lead to financial well-being. Financial literacy comprises of knowledge, behaviour and attitude. As the financial environment is getting more complicated and with the rising figures of household debt, the need for empowering consumers in making the right financial decisions becomes more critical than ever. One of the ways to empower consumers in making right financial decisions is by providing financial education which will then improve financial knowledge, behavior and attitude which leads to financial well-being ultimately. Credit Counselling and Debt Management Agency (AK.PK) has been providing financial education to aid the Central's Bank vision on creating a financially resilient consumer ultimately leading to vision of "Make Prudent Financial Management A Way of Life". AKPK"s financial education are designed and catered to fit specific live events as financial needs changes according to life stages. However, there are also arguments that financial literacy can be improved through experience and age, the need of financial education intervention is not much of an impact. As to that this study was conducted to see the relationship of financial education towards financial knowledge, behavior and attitude. The research also wanted to look at if financial knowledge, behavior and attitude a positive relationship towards financial well-being. This study has been made to find out the significant factors of financial education and financial well-being among students from higher learning institutions. The population group for this study are students who have participated in financial education by AKPK and of those who have not. The results from the research indicates that financial knowledge, behavior and attitude has a positive relationship towards financial well-being and also with financial education, students have better financial knowledge, behavior and attitude. However, the results also suggest that for future research the aspect of social and demographic of the participants to measure the influence on financial well-being as well.